ICTV Virus Taxonomy Profile: Botourmiaviridae. (24th May 2020) - Ayllón, María A.; Turina, Massimo; Xie, Jiatao; Nerva, Luca; Marzano, Shin-Yi Lee; Donaire, Livia; Jiang, Daohong; Consortium, ICTV Report
Abstract : The family Botourmiaviridae includes viruses infecting plants and filamentous fungi containing a positive-sense, ssRNA genome that can be mono- or multi-segmented. Genera in the family include: Ourmiavirus (plant viruses), and Botoulivirus, Magoulivirus and Scleroulivirus (fungal viruses). This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the taxonomy of the family Botourmiaviridae, which is available at ictv.global/report/botourmiaviridae .